Pengaruh Komunikasi Interpersonal Guru-Siswa dan Dukungan Teman Sebaya terhadap Minat Belajar Siswa SD Kelas II di Indonesia Pada Masa Pandemi Covid-19 - Mangaria, Sebrita (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2023)
Learning interest of elementary school students during the covid-19 pandemic has emerged as a new problem at school of Kanaan Foundation. The learning interest, especially second grade elementary school students, has decreased as distance learning being implemented. This research seeks to determine whether teacher-student interpersonal communication has an effect on student learning interest, whether peer support has an effect on student learning interest, and whether teacher-student interpersonal communication and peer support simultaneously have an effect on student learning interest of second grade elementary school students at school of Kanaan Foundation during the Covid-19 pandemic. This research applied quantitative design with the subjects involved were eighty five second grade elementary school students. Data collection was done using questionnaire in Likert scale. The research results revealed that teacher-student interpersonal communication and peer support variables had positive and significant effect on learning interest of second grade elementary school students with medium category for interpersonal communication (0.049) and low category for peer support (0.035). Simultaneously, interpersonal communication and peer support variables had an effect on student learning interest. The contribution of interpersonal communication was 16.747% and peer support was 8.40% on student learning interest.